2012
DOI: 10.3892/ol.2012.553
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of bevacizumab prolongs survival in an in vivo model of platinum pre-treated ovarian cancer

Abstract: Abstract. Ovarian cancer patients often suffer from malignant ascites and pleural effusion. Apart from worsening the outcome, this condition frequently impairs the quality of life in patients who are already distressed by ovarian cancer. This study investigated whether single intraperitoneal administration of the anti-VEGF antibody bevacizumab is capable of reducing the ascites-related body surface and prolonging survival. The study was performed in an orthotopic murine model of peritoneal disseminated platin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Nevertheless, it is conceivable that these different amounts of serum sEpCAM might pass through the peritoneal barrier and accumulate in the peritoneal cavity to even higher concentrations in patients with malignant ascites driven by the high oncotic pressure. Similar concentrations as for sEpCAM were described for the soluble VEGF protein in ascites [ 26 ] but, in contrast to the observations made with catumaxomab, binding of VEGF by bevacizumab seems to positively impact the course of the disesase [ 27 ].…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, it is conceivable that these different amounts of serum sEpCAM might pass through the peritoneal barrier and accumulate in the peritoneal cavity to even higher concentrations in patients with malignant ascites driven by the high oncotic pressure. Similar concentrations as for sEpCAM were described for the soluble VEGF protein in ascites [ 26 ] but, in contrast to the observations made with catumaxomab, binding of VEGF by bevacizumab seems to positively impact the course of the disesase [ 27 ].…”
Section: Discussionmentioning
confidence: 60%
“…Given the fact that the effects of bevacizumab monotherapy were not found to be significantly dependent on whether the drug is intravenously or intraperitoneally administered [ 59 ], we proceed with the reproduction of the results of a series of in vivo experiments in mice intraperitoneally treated with bevacizumab. In particular, eight in vivo experiments conducted in mice bearing breast (KPL-4 cell line), lung (H226 cell line), head and neck (SCC1 cell line) as well as colon (HCT116, HT29, HCP40 and HP40 cell lines) tumour xenografts have been selected from relevant literature [ 60 – 62 ] in order to fit the model to actual experimental data.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that the level of circulating VEGF correlates with the severity of CASS in tumor-bearing mice and human cancer patients, and that anti-VEGF agents could improve organ function (8). As a consequence of the off-tumor target effects, improvements to organ function and alterations in chemotoxic tolerance may be the most important mechanisms with a survival benefit in cancer patients with CASS (8,24).…”
Section: Discussionmentioning
confidence: 99%